2019
DOI: 10.5114/wiitm.2019.85540
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic D2 plus complete mesogastrium excision using the "enjoyable space" approach versus conventional D2 total gastrectomy for local advanced gastric cancer: short-term outcomes.

Abstract: Introduction: Laparoscopy-assisted radical total gastrectomy is technically demanding. Aim: To introduce the "enjoyable space" approach to achieve D2 plus complete mesogastrium excision (CME) and to investigate its safety and feasibility. Material and methods: Between January 2015 and December 2017, 165 patients with primary advanced upper gastric cancer underwent laparoscopy-assisted radical total gastrectomy. Among these patients, 81 underwent conventional D2 total gastrectomy (D2 group) and 84 underwent D2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Zheng et al . [ 26 ] confirmed that laparoscopic D2 plus complete mesogastrium excision had lower intraoperative blood loss and a higher number of lymph nodes than conventional D2 total gastrectomy. Nevertheless, traditional laparoscopy brings some challenges to surgeons, such as limited manipulation and ergonomic discomfort.…”
Section: Discussionmentioning
confidence: 97%
“…Zheng et al . [ 26 ] confirmed that laparoscopic D2 plus complete mesogastrium excision had lower intraoperative blood loss and a higher number of lymph nodes than conventional D2 total gastrectomy. Nevertheless, traditional laparoscopy brings some challenges to surgeons, such as limited manipulation and ergonomic discomfort.…”
Section: Discussionmentioning
confidence: 97%
“…Laparoscopic gastrectomy is a complex procedure that includes lymph node dissection and various intestinal anastomoses [ 17 , 18 ], requiring a considerable learning curve to overcome [ 1 , 15 ]. The learning curve, the definition of which is clearly arbitrary, depends on factors such as the talent of surgeons, quality of teaching programs, and amount of experience of the surgeons [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enjoyable space approach and SPLT reconstruction have been reported previously in the literature [ 10 , 19 ]. The procedure can be briefly described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Although the prognosis of colorectal cancer has significantly improved due to the widespread application of complete mesenteric excision, the concept and importance of complete mesogastrium excision (CME) have not yet been widely recognized and effectively evaluated in curative gastrectomy [15][16][17][18]. Our previous study presented the "enjoyable space" approach to achieve D2 + CME and confirmed its feasibility and safety in the LATG procedure [19]. However, this technique has not yet been further appraised in TLTG.…”
Section: Introductionmentioning
confidence: 98%